Legal aspects of Forensics - Siniša Franjić (Forensic Science Today - Peertechz Publications, 2018)
Forensics is the scientific discipline concerned with proving criminal offenses. It proves in a way that an investigator collects, documents and analyzes all facts related to the crime. The most important task of the investigator is to collect the largest possible number of pieces of evidences that connect to a criminal offense. They are mostly found at the site of criminal events, and in technical terms, is called physical evidence. Based on these sets hypotheses that connect one fact with another, and then we come to the theory that explains the nature of the criminal acts. Forensic proof of crimes are very complex transaction with the ultimate goal to prove or disprove the offense and find the perpetrators.